PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BAAMBOOZLE TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN PENDIDIKAN PANCASILA DI UPT SMP NEGERI 024 SIHONONGAN - Pebryna Riosa Siburian; Liber Siagian; Prayetno; Surya Dharma; Jamaludin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to determine the effect of using Baamboozle learning media on student learning outcomes in the Pancasila Education subject at UPT SMP Negeri 024 Sihonongan. The research focuses on cognitive learning outcomes—specifically, students' knowledge regarding the Pancasila Education curriculum. A quantitative approach with a quasi-experimental pretest-posttest design was employed. Class VII-B (32 students) served as the experimental group, while Class VII-C (31 students) served as the control group; both classes were selected using purposive sampling. Data collection instruments included test sheets, observation, and documentation. The results indicate that the use of Baamboozle learning media had a significant effect on the Pancasila Education learning outcomes of Grade VII students at UPT SMP Negeri 024 Sihonongan. This is evidenced by the increase in average scores in the experimental class using Baamboozle—rising from 50.25 in the pretest to 89.25 in the posttest—compared to the control class, which saw an increase from 54.45 to 77.94. Normality test results showed the data to be normally distributed (significance value > 0.05), and homogeneity test results indicated the data were homogeneous (significance value 0.330 > 0.05). Furthermore, the Independent Samples t-test yielded a Sig. (2-tailed) value of 0.000 (< 0.05); consequently, the alternative hypothesis (Hₐ) was accepted, and the null hypothesis (H₀) was rejected. These findings demonstrate that Baamboozle learning media significantly influences the improvement of student learning outcomes. Additionally, the use of Baamboozle enhances student motivation, active participation, collaboration, and thinking skills through interactive, game-based learning.